Job crafting, psychological capital and work engagement: an empirical evidence of a sustainable high-performance GLC / Norashikin Hussein and Nur Suhaila Amiruddin - Hussein, Norashikin; Amiruddin, Nur Suhaila (Universiti Teknologi Mara Selangor, 2020)
Malaysian government-linked companies (GLCs) are expected to not only sustain their performance but also to contribute more on the long term business and societal value. Thus, in moving towards this direction, the organisation needs employees that are energetic and have a secure positive connection to their job. This study aims to determine job and individual-related factors that influence an individual work engagement. Specifically, this study aims at determining the (1) relationship between job crafting and work engagement; (2) relationship between psychological capital and work engagement. Data were collected from 201 executives level employees of a high-performance GLC in Malaysia. The findings revealed that employees need to have self-efficacy and optimism in order to be engaged in their work. Additionally, social job resources such as feedback and support are also found to be crucial to create high work engagement workforce. This study is significant to the top management, human resource practitioners, managers and supervisors in the understanding job and individual factors that would lead to work engagement. This input is also beneficial in designing jobs and creating programs that would lead to high work engagement among employees.